Temporal Shotgun Metagenomics Revealed the Potential Metabolic Capabilities of Specific Microorganisms During Lambic Beer Production - De Roos, Jonas; Verce, Marko; Weckx, Stefan; De Vuyst, Luc (Frontiers in Microbiology, 2020)
Lambic beer production processes are characterized by a temporal succession of well-adapted microbial species. Temporal metagenomic analysis of a Belgian, traditional, lambic beer production process, which was examined microbiologically and metabolomically before, confirmed that the microbial diversity is limited. Moreover, it allowed to link the consumption and production of certain compounds to specific microbial groups or species. Fermentation characteristics, such as the conversion of malic acid into lactic acid and acetoin production, were retrieved and could be attributed to specific microorganisms, namely Pediococcus damnosus and Acetobacter species, respectively. Traits previously ascribed to brewery-specific Dekkera bruxellensis strains were confirmed during the lambic beer production process examined multiphasically; in particular, the higher production of 4-ethylguaiacol compared to 4-ethylphenol was further shown by mass spectrometric analysis. Moreover, the absence of phenolic acid decarboxylase in Brettanomyces custersianus was shown culture-independently and could explain its late occurrence during the maturation phase. Furthermore, the potential of maltooligosaccharide degradation could be ascribed metagenomically to not only Brettanomyces species but also Saccharomyces kudriavzevii, possibly explaining their degradation early in the lambic beer production process. Also, acetic acid bacteria (AAB) seemed to be able to consume maltooligosaccharides via their conversion into trehalose. Furthermore, these AAB possessed esterase genes, potentially capable of forming ethyl acetate, which may contribute to the flavor of lambic beer. Improved knowledge on the reasons behind certain community dynamics and the role of the different microorganisms in terms of potential functionality could improve brewery practices to assure to produce more quality-stable end-products.